2007
DOI: 10.1080/02699050701201813
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive interventions post acquired brain injury

Abstract: Future research should explore functional outcome measures and long-term effects of treatment interventions through follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 69 publications
4
82
0
2
Order By: Relevance
“…Although the effectiveness of cognitive rehabilitation is documented within some domains following ABI, there is still a paucity of empirical evidence for the efficacy of interventions for rehabilitation of EF (Cicerone et al, 2011;Rees, Marshall, Hartridge, Mackie & Weiser, 2007; Wilson, 2008). Reviews recommend metacognitive strategy training including self-monitoring and self-regulation as practice standard following ED due to traumatic brain injury (TBI) (Cicerone et al, 2011;Kennedy et al, 2008).…”
Section: Tornås-goal Management Training In Abimentioning
confidence: 99%
“…Although the effectiveness of cognitive rehabilitation is documented within some domains following ABI, there is still a paucity of empirical evidence for the efficacy of interventions for rehabilitation of EF (Cicerone et al, 2011;Rees, Marshall, Hartridge, Mackie & Weiser, 2007; Wilson, 2008). Reviews recommend metacognitive strategy training including self-monitoring and self-regulation as practice standard following ED due to traumatic brain injury (TBI) (Cicerone et al, 2011;Kennedy et al, 2008).…”
Section: Tornås-goal Management Training In Abimentioning
confidence: 99%
“…A wristwatch with a total of 6 alarms (sound and vibrations) was programmed to remind medication twice a day (9). The participant needed to take the medication at once when the watch alarmed and, therefore, was the most appropriate to use.…”
Section: Taking Medication Punctually By the Use Of A Wristwatch Withmentioning
confidence: 99%
“…In reviewing the literature about the use and efficency of AT or ET in the form of electronic aids in people with ABI, it was found that a variety of AT, such as palmtop computer, paging system, voice organizer, can reduce memory problems [9,[15][16][17][18][19]. To the best of our knowledge, only one study has used unmodified handheld computers off-the-shelf to compensate for disabilities in people with ABI [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have attempted to develop strategies for improvement of memory impairment in patients with TBI 2) . These strategies include computerbased memory training programs, therapist-assisted memory training, cholinergic drugs, and memory aids including a notebook, appointment diary, or to-do-list [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%